A 'probabilistic' approach to the use of econometric models in sunset reviews - Alexander Keck; Bruce Malashevich; Ian Gray (World Trade Organization (WTO), 2006)
Economists have increasingly become involved in trade remedy and litigation matters that call for economic interpretation or quantification. The literature on the use of econometric methods in response to legal requirements of trade policy is rather limited. This article contributes to filling this gap by demonstrating the efficacy of using a simple `probabilistic' model in analyzing the `likelihood' of injury to the local industry concerned, following a finding of continuation or recurrence of dumping (or countervailable subsidies). The legal concept of `likelihood' is not only particularly well-suited to illustrate the systemic need for trade lawyers and economists to cooperate. It is also of imminent practical relevance with a groundswell of `sunset' reviews looming on the horizon. We discuss the significance of economic analysis for trade remedy investigations by reviewing the literature, the applicable WTO rules and, in particular, the pertinent case law. The potential value of probabilistic simulations for `likelihood' determinations is exemplified using a real-world application. Using data from past United States International Trade Commission investigations, we find that a probabilistic model that takes account of the uncertainty surrounding economic parameters reduces the risk of misjudging the effect on the domestic industry of a termination of trade remedies.
Keywords: F13; F14; F17; K33; 330; Trade remedies; economic modeling; WTO; injury